2020
DOI: 10.1080/23311975.2020.1781993
|View full text |Cite
|
Sign up to set email alerts
|

Does teacher competence and commitment improve teacher’s professionalism

Abstract: This study aims to examine and analyze the role of teacher competence and commitment in supporting teacher performance. The study was conducted on professional teachers in Madrasah schools in all regencies/cities in Bali which total of 906 teachers. The number of samples was determined based on the Slovin formula at an error rate of 5%, obtained 277 teachers distributed proportionally in 9 districts/cities. Data collection is done by direct interview based on a questionnaire that has been prepared. The collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 21 publications
5
39
0
6
Order By: Relevance
“…Previous studies revealed that competencies could significantly contribute to the quality of teaching performance (Siri et al, 2020). Teaching competencies boost learning activities and motivate teachers to create remarkable contributions with their performance (Hakim, 2015).…”
Section: Teaching Competenciesmentioning
confidence: 99%
“…Previous studies revealed that competencies could significantly contribute to the quality of teaching performance (Siri et al, 2020). Teaching competencies boost learning activities and motivate teachers to create remarkable contributions with their performance (Hakim, 2015).…”
Section: Teaching Competenciesmentioning
confidence: 99%
“…"Teacher competence and commitment have significantly positive effect on the performance of professional teachers… It is necessary to support the improvement of the competence and commitment of teachers" (Siri, Supartha, Sukaatmadja & Rahyuda, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, competence is one of the key erudition qualities of a teacher of a tertiary educational institution. Studies prove that competence is the trait of an educator that indicates the appropriate level of knowledge, as well as the acquired skills and practical abilities that he / she possesses and properly directs to the learning process (Siri, Supartha, Sukaatmadja & Rahyuda, 2020). "Teachers' competence in educational assessment is a key feature in teacher professionalism" (DeLuca, Schneider, Coombs, Pozas & Rasooli, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of them is pedagogical competence which can help them face the diversity of students especially in elementary schools (Mumpuniarti, Handoyo, Pinrupitanza, & Barotuttaqiyah, 2020). In recent years, the teachers' quality and effectiveness have been the major issue in educational settings (Dutta, Halder, & Sen, 2017;Mahgoub & Alyas, 2014;Siri, Supartha, Sukaatmadja, & Rahyuda, 2020). Further, the teacher performance and teacher effectiveness are utilized as the basis for decisions about continued employment, tenure and promotion, and financial aspect (Morgan, Hodge, Trepinski, & Anderson, 2014).…”
Section: Introductionmentioning
confidence: 99%